Rehabilitation of Discharged Patients With Chronic Obstructive Pulmonary Disease-Are New Strategies Needed? - Lars Morsø; Morten Sall Jensen; Christian von Plessen; Peter Qvist (SAGE Publishing, 2017)
Background: Rehabilitation after hospital stay implies several benefits for patients with chronic obstructive pulmonary disease (COPD); still few patients are referred and participate in rehabilitation programs. We conducted a case study to investigate the effects of interventions targeting the referral, uptake, and completion for a program of early rehabilitation in the primary health-care sector. Methods: We undertook targeted initiatives to make patients participate in an individualized rehabilitation program with gradual increased intensity. After discharge, primary care COPD nurses and physiotherapists guided patients through progressing exercises in small groups online. Patients proceeded to class-based exercises, patient education and/or leisure activities, or continued telerehabilitation. We evaluated the effects of the intervention by assessing referral rates, completion, and readmission. Results: Sixteen (23% of discharged patients) patients were referred to rehabilitation. In comparison, only 1 (0.8%) in 131 patients from Vejle hospital was referred to Vejle hospital. Twelve patients completed rehabilitation, all having severe COPD. All started the program within 2 weeks and proceeded to the online-guided exercises within 4 weeks. Study data showed that after 30 days, 1 (6.3%) of the 16 patients in the rehabilitation program had been readmitted compared to 8 (14.8%) of 55 patients who were not referred. After 90 days, 2 (12.5%) and 11 (20.0%) patients were readmitted, respectively. The readmission rate showed a nonsignificant decline in patients participating in rehabilitation. Conclusion: This case study showed that the referral rate of patients with COPD to early municipal rehabilitation is extremely low without a targeted effort and still insufficient in spite of a focused intervention. We showed that completion of a municipal rehabilitation program shortly after discharge is possible even for patients with severe COPD. The findings from our pilot study can guide further investigations into the effect of implementation strategies for handovers between health-care sectors to secure early-onset rehabilitation of patients with COPD.